A High Capacity Aluminum‐Ion Battery Based on Imidazole Hydrochloride Electrolyte. Issue 13 (5th July 2019) - Xu, Cheng; Zhao, Shimeng; Du, Yiqun; Zhang, Wenyang; Li, Pan; Jin, Huixin; Zhang, Youjian; Wang, Zihan; Zhang, Jianxin
Abstract: Aluminum‐ion batteries (Al‐ion batteries) have become a potential energy storage system, owing to their excellent cycling performance, three‐electron‐redox properties, and safety performance. Until now, great progress has been made in Al‐ion batteries. However, the Al‐ion battery system still encounters various problems, such as high electrolyte price, harsh working environment, low discharge platforms, and inferior capacity. Here, we prepared a novel Al‐ion battery with AlCl3 /Imidazole hydrochloride (ImidazoleHCl) as the electrolyte, aluminum as the negative electrode, and commercial graphite as the positive electrode. The battery achieves a high specific discharge capacity of 129 mA h g −1 at a current density of 0.5 A g −1 and 105 mA h g −1 with a high coulombic efficiency of 99 % at the current density of 4 A g −1 after 1000 cycles. The mechanism of AlCl4 − intercalation/de‐intercalation is proved by Raman, XRD and EDS studies. ImidazoleHCl is a promising electrolyte and this work provides a new insight for the Al‐ion battery system. Abstract : Al‐ternative battery technology : An aluminum‐ion battery with ionic liquid AlCl3 /imidazole hydrochloride as the electrolyte exhibits a good performance at a current density of 4 A g −1 and 105 mA h g −1 with a high coulombic efficiency of about 99 % after 1000 cycles.